Partial nephrectomy in frail patients: Benefits of robot-assisted surgery. (September 2021) - Rosiello, Giuseppe; Palumbo, Carlotta; Deuker, Marina; Stolzenbach, Lara Franziska; Martin, Thomas; Tian, Zhe; Larcher, Alessandro; Capitanio, Umberto; Montorsi, Francesco; Shariat, Shahrokh F.; Kapoor, Anil; Saad, Fred; et al.
Abstract: Background: To compare the effect of robot-assisted (RAPN) vs. open (OPN) partial nephrectomy on short-term postoperative outcomes and total hospital charges in frail patients with non-metastatic renal cell carcinoma (RCC). Methods: Within the National Inpatient Sample database we identified 2745 RCC patients treated with either RAPN or OPN between 2008 and 2015, who met the Johns Hopkins Adjusted Clinical Groups frailty-defining indicator criteria. We examined the rates of RAPN vs. OPN over time. Moreover, we compared the effect of RAPN vs. OPN on short-term postoperative outcomes and total hospital charges. Time trends and multivariable logistic, Poisson and linear regression models were applied. Results: Overall, 1109 (40.4%) frail patients were treated with RAPN. Rates of RAPN increased over time, from 16.3% to 54.7% (p < 0.001). Frail RAPN patients exhibited lower rates (all p < 0.001) of overall complications (35.3 vs. 48.3%), major complications (12.4 vs. 20.4%), blood transfusions (8.0 vs. 13.5%), non-home-based discharge (9.6 vs. 15.2%), shorter length of stay (3 vs. 4 days), but higher total hospital charges (50, 060 vs. 45, 699). Moreover, RAPN independently predicted (all p < 0.001) lower risk of overall complications (OR: 0.58), major complications (OR: 0.55), blood transfusions (OR: 0.60) and non-home-based discharge (OR: 0.51), as well as shorter LOS (RR: 0.77) but also higher total hospital charges (RR: +7682), relative to OPN. Conclusions: In frail patients, RAPN is associated with lower rates of short-term postoperative complications, blood transfusions and non-home-based discharge, as well as with shorter LOS than OPN. However, RAPN use also results in higher total hospital charges. Highlights: Frail patients who undergo major surgery are increasing over time. Robot-assisted approach reduces overall and major complications. In frail patients robotic surgery predicts better short-term postoperative outcomes. The use of robot-assisted surgery increases total hospital charges.